Train simulator using P.I.C microcontroller - Abd Hamid, Muhammad Zulkifli (2009)
This final year project performs the basic movements and operations of a train simulation system by employing a P.I.C microcontroller. Programming technique, digital system design, structural and mechanical designs were developed to suit the operation of the train simulation itself. The heart of this project is the PIC16F877A chip. A final comment on the prospect of the development is presented.